Effects of negative emotional valence on readers’ text processing and memory for text: an eye-tracking study - Arfé, Barbara; Delatorre, Pablo; Mason, Lucia (Reading & writing, 2023)
Comprehension of stories requires readers to take the perspective of the story characters and imagine or feel their cognitive and affective states. The study investigated how variations in emotional valence within a literary text affected readers’ global text processing, as reflected in their eye movements during the first and second-pass reading, and their memory for text. Processes of reading were also examined in relation to readers’ dispositional empathy. Undergraduate students (N = 42) were assigned to an emotionally negative or neutral reading condition. They read a natural text passage from a suspense story while their ocular behavior was registered. After reading, they responded to multiple-choice questions assessing their memory of the text. Results revealed longer first-pass fixation times for content evoking negative emotions than for neutral content, which could be suggestive of a more analytical processing of the former. These effects were however local and did not impact the processing of the text at global level. Memory for the emotionally negative content was more accurate than memory for the neutral content. Dispositional empathy did not contribute to reading processes and outcome. Findings are discussed against the mixed results in the current literature and practical implications are also outlined.